2021
DOI: 10.1038/s41586-021-03814-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin neurons enable social transmission of maternal behaviour

Abstract: Maternal care, including by non-biological parents, is important for offspring survival1–8. Oxytocin1,2,9–15, which is released by the hypothalamic paraventricular nucleus (PVN), is a critical maternal hormone. In mice, oxytocin enables neuroplasticity in the auditory cortex for maternal recognition of pup distress15. However, it is unclear how initial parental experience promotes hypothalamic signalling and cortical plasticity for reliable maternal care. Here we continuously monitored the behaviour of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 40 publications
(55 reference statements)
10
134
0
Order By: Relevance
“…Additionally, prairie voles exposed to a stressed partner engaged in more partner-directed social grooming behavior – an effect modulated by OT in the ACC ( Burkett et al, 2016 ). A recent study demonstrated that the social transmission of maternal behavior, including the visual observation and acquisition of this behavior, was mediated by PVN OT ( Carcea et al, 2021 ), supporting the pivotal role by OT in facilitating the social transmission of information and influencing social contagion.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, prairie voles exposed to a stressed partner engaged in more partner-directed social grooming behavior – an effect modulated by OT in the ACC ( Burkett et al, 2016 ). A recent study demonstrated that the social transmission of maternal behavior, including the visual observation and acquisition of this behavior, was mediated by PVN OT ( Carcea et al, 2021 ), supporting the pivotal role by OT in facilitating the social transmission of information and influencing social contagion.…”
Section: Discussionmentioning
confidence: 90%
“…For demonstration and validation, we applied our analysis pipeline to barrel cortex neurons, and were able to recover expected neural tuning to (lateralized) whisker touch and movement 59 . Our end-to-end tracking method and analysis pipeline maps tuning to movements and postures of the partner’s body, and is thus ideally suited to detect potential social interaction systems such as rodent ‘mirror neuron’ signals in other brain areas 70 , 71 . The 45 predictor features that we have included in our analysis pipeline could be expanded to add additional features of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Selective recording of OT neuronal activity during social behavior has only recently been made possible ( Carcea et al, 2021 ; Resendez et al, 2020 ; Tang et al, 2020 ) thanks to the employment of recombinant adeno-associated viral (rAAVs) vectors that achieve specific expression of transgenes in OT neurons, in combination with electrophysiology or calcium imaging techniques. The two methods that we use for cell-type specific recording in freely moving animals are extracellular recordings of action potentials combined with optogenetic tagging (opto-tagging) ( Lima et al, 2009 ) and imaging of genetically encoded calcium indicators (GECIs) ( Chen et al, 2013 ), such as GCaMP6s, with fiber photometry.…”
Section: Before You Beginmentioning
confidence: 99%